Influence of seed nano-crystals on electrical properties and phase transition behaviors of Ba0.85Sr0.15Ti0.90Zr0.10O3 ceramics prepared by seed-induced method - Krit Sutjarittangtham (2018)
© 2015, The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht. This work studied the effects of seed nano-crystal on the electrical properties and the phase transition behaviors of Ba0.85Sr0.15Ti0.90Zr0.10O3 (BSZT) ceramics. The BSZT ceramics were prepared by the seed-induced method. The seed nano-crystal were prepared by the molten salt technique, and NaCl-KCl (1:1 by mole) eutectic mixtures were used as the flux.[1] The ceramic powders were prepared by using a conventional method which added seed nano-crystals at various ratios. Results indicated that seed nano-crystals enhanced the electrical properties of ceramics. The sample with a 20 wt. % seed nano crystals has excellent value of dielectric constant (µr) of 34698 at maximum temperature. The phase transition temperature was observed at 60°C. The morphology was found that the grain size increasing significantly with an increased of seed nano crystals. The relaxor ferroelectric phase transition behavior was shown by a diffuseness parameter (³). An increase in the BSZT-seed showed a decreased in ³ value from 1.61 to 1.44. Thus the ferroelectric of the BSZT ceramics can be confirmed by hysteresis loop.